Thermal conductivity of dc-plasma assisted chemical vapor deposited diamond films - Chae, H.-B.; Han, Y.-J.; Seong, D.-J.; Kim, J.-C.; Baik, Y.-J. (1995)
The dc-plasma assisted chemical vapor deposition method has been used to synthesize diamond films. Thermal diffusivity of these films has been measured in 120-800 K with a modified Angstrom method. Phonon scattering processes are considered to analyze thermal conductivity with the full Callaway model. In analysis, microstructure of grain boundaries and extended defect concentration give significant effects to the mean free path of phonons in low temperatures. At high temperatures, the thermal conductivity is governed by the intrinsic thermal resistive process, the umkalpp process. Thermal conductivity of the films above 500 K is shown to close to a recent measurement of natural diamond. This supports that the crystal structure of the films is not different with the bulk diamond. ？ 1995 American Institute of Physics.